2016
DOI: 10.1248/bpb.b15-00842
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Underlying Induction of Hyperglycemia in Rats by Single Administration of Olanzapine

Abstract: Acute administration of olanzapine rapidly elevates blood glucose levels. However, the mechanism underlying the rapid development of hyperglycemia with the administration of olanzapine remains unclear. The aim of the present study was to clarify the mechanism underlying olanzapine-induced acute hyperglycemia. Male Wistar rats received an intravenous infusion of saline (control) or olanzapine 2.5, 5, or 10 mg/kg. Blood samples were obtained periodically after olanzapine infusion to determine serum concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…Our previous reports demonstrated that fluoroquinolone antimicrobial agents can induce histamine release leading to an increase in serum epinephrine concentrations and hyperglycemia. [7][8][9] In contrast, a single intravenous injection of clozapine increased the serum glucose levels without histamine release. Olanzapine also induced hyperglycemia without affecting the serum concentration of histamine.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous reports demonstrated that fluoroquinolone antimicrobial agents can induce histamine release leading to an increase in serum epinephrine concentrations and hyperglycemia. [7][8][9] In contrast, a single intravenous injection of clozapine increased the serum glucose levels without histamine release. Olanzapine also induced hyperglycemia without affecting the serum concentration of histamine.…”
Section: Discussionmentioning
confidence: 95%
“…We previously reported that novel fluoroquinolone antimicrobial agents such as gatifloxacin, levofloxacin, and moxifloxacin increased serum glucose concentrations in rats, in association with the induction of histamine release by these drugs, leading to elevations in serum adrenaline concentrations. [6][7][8][9] In contrast, a single intravenous injection of olanzapine increased the serum glucose and adrenaline levels without histamine release. 10) These results suggest that the mechanisms responsible for drug-induced elevations in serum glucose levels vary among these drugs.…”
mentioning
confidence: 95%
“…This caused acceleration of atherosclerosis and the onset of ischemic diseases. These drugs have been involved in weight gain, abdominal obesity, dyslipidemias and have increased insulin resistance, hepatic glucose production and the level of blood sugar [47][48][49] .…”
Section: Cardiometabolic Effectsmentioning
confidence: 99%
“…These studies demonstrated that serum glucose concentrations have been greater because of a higher hepatic gluconeogenesis via the sympatethic nervous system. Also, changing the fatty acid profile by increasing saturated fats could play a role in insulin resistance 49 .…”
Section: Mechanisms Of Cardiometabolic Effectsmentioning
confidence: 99%
“…▶ Tab. 2 Unerwünschte metabolische Wirkungen der in Deutschland am häufigsten verordneten Antipsychotika auf der Basis der Angaben in Fachinformationen (modifiziert nach [2,34,35] [42]. Zudem scheint Olanzapin das Verhältnis der Fettsäuren (gesättigt/ungesättigt) zu modifizieren, wodurch eine Insulinresistenz begünstigt wird [43].…”
Section: Wirkstoffunclassified